La escuela de jurisprudencia de Michoacán y la enseñanza del derecho - García Figueroa, Héctor Daniel (Universidad Michoacana de San Nicolás de Hidalgo, 2007)
The research that follows in the following pages, responded to the concern to explore an unknown stage on the teaching of Law in the state of Michoacán; This, in order to unravel specific characteristics of the School of Jurisprudence of the entity in the early twentieth century. Aspects aimed mainly at determining if in that institution had been implemented teaching methods with their own peculiarities, which, combined with various elements, made possible an unimaginable stage known as the Golden Age, because they were the bases of an institutional prestige that even In our days is a reference of academic excellence. The beginning of this research was complicated because the existing bibliography did not refer in concrete form to characters that needed the object of study; Nor even as indicators, because in the initial plan of study was based on indications, that is, from various elements of reference to the possible existence of a period of high academic level in legal education in Michoacan. Notwithstanding the foregoing, we continued the search for components that evidenced the academic boom of that time. After a long period of field work and a constant search for sources, it was possible to compile the material that would allow to present the information that is shown in the following pages. Both the first and second chapters are an adherence to the scheme presented in the research project, and their inclusion is due to the fact that both indicate the origin and evolution of legal education in Michoacán. In this sense, the present investigation begins with a chapter that analyzes and exposes enough elements to affirm that the teaching of Law in the State arose from the sixteenth century - probably from the second half of that century - with the implementation of Chair of Penitential Canons that was given in the College of San Nicolás, as arranged by Don Vasco de Quiroga, for the studies of clerical formation.

La investigación que se vierte en las siguientes páginas, respondió a la inquietud de explorar una etapa desconocida sobre la enseñanza del Derecho en el estado de Michoacán; esto, con el fin de desentrañar características específicas de la Escuela de Jurisprudencia de la entidad a principios del siglo XX . Aspectos dirigidos, principalmente, a determinar sí en dicha institución se habían implementado métodos de enseñanza con particularidades propias, las cuales, sumados a diversos elementos, hicieron posible una etapa inimaginable conocida como Época de Oro, porque fueron las bases de un prestigio institucional que aun en nuestros días es referencia de excelencia académica. El inicio de esta investigación fue complicado porque la bibliografía existente no refería en forma concreta a caracteres que precisaran el objeto de estudio; ni aun como indicadores, porque en el plan inicial de estudio se partió de indicios, es decir, de diversos elementos de referencia a la posible existencia de un período de alto nivel académico en la enseñanza jurídica en Michoacán. No obstante lo anterior, se continuó en la búsqueda de componentes que evidenciaran el auge académico de ese tiempo. Después de un largo período de trabajo de campo y de una búsqueda constante de fuentes, se logró recopilar el material que permitiera presentar la información que se muestra en las siguientes páginas. Tanto el primer capítulo como el segundo constituyen una adhesión al esquema presentado en el proyecto de investigación, y su inclusión obedece a que en ambos se precisan el origen y evolución de la enseñanza jurídica en Michoacán. En este sentido, la presente investigación inicia con un capítulo donde se analizan y exponen suficientes elementos para afirmar que la enseñanza del Derecho en el Estado surgió a partir del siglo XVI -probablemente desde la segunda mitad de ese siglo-, con la implementación de la cátedra de Cánones Penitenciales que se impartía en el Colegio de San Nicolás, según lo dispuesto por Don Vasco de Quiroga, para los estudios de la formación clerical.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2007-0008; Enseñanza; Jurisprudencia; Cátedra; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/437